INVENTING OURSELVES : The Secret Life of the Teenage Brain - Blakmore, Sarah-Jayne (London : Doubleday, 2018)
Drawing upon her cutting-edge research in her London laboratory, award-winning neuroscientist, Sarah-Jayne Blakemore explains what happens inside the adolescent brain, and what her team's experiments have revealed about our behaviour, and how we relate to each other and our environment as we go through this period of our lives. She shows that while adolescence is a period of vulnerability, it is also a time of enormous creativity - one that should be acknowledged, nurtured and celebrated. Our adolescence provides a lens through which we can see ourselves anew.
Keywords: Neurosciences -- Popular works; Brain -- Popular works -- Growth; Adolescent psychology